2014
DOI: 10.1177/1535370214523703
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin: Powerful protection of ischemic and post-ischemic brain

Abstract: Ischemic brain injury inflicted by stroke and cardiac arrest ranks among the leading causes of death and long-term disability in the United States. The brain consumes large amounts of metabolic substrates and oxygen to sustain its energy requirements. Consequently, the brain is exquisitely sensitive to interruptions in its blood supply, and suffers irreversible damage after 10–15 minutes of severe ischemia. Effective treatments to protect the brain from stroke and cardiac arrest have proven elusive, due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 174 publications
(287 reference statements)
1
37
0
1
Order By: Relevance
“…For example, HIF-1-driven expression of glycolytic enzymes 122 could increase O 2 -independent ATP production, and erythropoietin, long recognized for its pivotal role in hematopoiesis, 123 also can be synthesized within the brain, where it exerts a host of neuroprotective actions. 124 IHT improves endothelial production of NO Normally, NO involved in cerebral blood flow regulation is produced by endothelial cells, neurons, and nitrergic perivascular nerves. 125 In addition to regulating cerebral blood flow, endothelial NO is vaso-and neuroprotective due to its antiplatelet, antithrombotic, antiproliferative, and antiatherosclerotic functions.…”
Section: Intermittent Hypoxic Training (Iht) Improves Cerebrovascularmentioning
confidence: 99%
“…For example, HIF-1-driven expression of glycolytic enzymes 122 could increase O 2 -independent ATP production, and erythropoietin, long recognized for its pivotal role in hematopoiesis, 123 also can be synthesized within the brain, where it exerts a host of neuroprotective actions. 124 IHT improves endothelial production of NO Normally, NO involved in cerebral blood flow regulation is produced by endothelial cells, neurons, and nitrergic perivascular nerves. 125 In addition to regulating cerebral blood flow, endothelial NO is vaso-and neuroprotective due to its antiplatelet, antithrombotic, antiproliferative, and antiatherosclerotic functions.…”
Section: Intermittent Hypoxic Training (Iht) Improves Cerebrovascularmentioning
confidence: 99%
“…Cardiocerebral resuscitation (CCR) and effective cardiac defibrillation reperfuse the ischemic brain, but reperfusion ignites an explosive burst of reactive oxygen, nitrogen and dicarbonyl formation which intensifies intracellular Ca 2þ overload, glutamate excitotoxicity and inflammation, culminating in extensive neuronal death. 2 However, numerous clinical trials failed to demonstrate appreciable neurocognitive benefits of antioxidant and antiinflammatory interventions after CA and CCR. 3,4 The powerful glycating dicarbonyl methylglyoxal, a product of spontaneous decomposition of the glycolytic intermediates glyceraldehyde 3-phosphate (GAP) and dihydroxyacetone phosphate (DHAP), has been implicated in the pathogenesis of Alzheimer's Disease, Parkinson's Disease, and other neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…10 Erythropoietin receptors are also expressed not only in hematopoietic cells but also in other types of cells, such as endothelial cells, neurons, and cardiomyocytes. [11][12][13] A series of studies using a mutant mouse that expresses the erythropoietin receptor exclusively in hematopoietic cells (EpoR −/− rescued) showed that deletion of the erythropoietin receptor aggravates I/R injury and Abstract-Chronic kidney disease (CKD) is known to increase myocardial infarct size after ischemia/reperfusion. However, a strategy to prevent the CKD-induced myocardial susceptibility to ischemia/reperfusion injury has not been developed.…”
mentioning
confidence: 99%